HUBUNGAN MINAT BELAJAR AQIDAH AKHLAK DENGAN MORALITAS SISWA KELAS V MI MATHLA’UL ANWAR SIBANTENG - Azis, Najmi; Dahlan R, M.; Marasabessy, Yusra (ATTA`DIB, 2018)
Many factors cause moral degeneration among students at this time, to prepare students to have a strong personality, quality and noble, madrasah as an Islamic educational institution needs to pay attention to the interest of learning on subjects Aqidah Akhlak. The purpose of this research is to know the correlation of learning interest of Aqidah Akhlak with morality of student in MI Mathla’ul Anwar Sibanteng. The research method used is quantitative, because the research data in the form of numbers and analysis using statistics. Type of research instrument using questionnaire and likert scale, while the approach is reaserch field. The research hypothesis formulated as follows is suspected to have a significant influence between the interest of learning Aqidah Akhlak with the morality of students based on rxy calculation of 0.44 number of correlation index obtained no negative sign, which lies between 0.40 to 0.69. Based on the correlation table product moment guidelines used, it can be said that between variables X and Y there is a correlation of moderate or moderate. See the value of xy obtained is 0.44 while the value of each table is 0.273 and 0.354. Thus it turns out the rxy at a significance level of 5% and at a significance level of 1% greater than the value of the table. Thus at a significance level of 5% and 1% Ha accepted and Ho rejected. Based on the analysis can be concluded that between the interest of learning Aqidah Akhlak with the morality of students there is a significant relationship with the level of correlation is enough or moderate.